DS-Modified Paeoniflorin pH-Responsive Lipid–Polymer Hybrid Nanoparticles for Targeted Macrophage Polarization in a Rat Model of Rheumatoid Arthritis - Zhang J; Yang J; Yu Z; Bai H; Wang Y; Wang R (International Journal of Nanomedicine)
Junhao Zhang,1,* Jing Yang,2,* Zhoubo Yu,1 Haotian Bai,1 Yanhong Wang,1,3 Rui Wang1,3 1College of Pharmacy, Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, 150040, People’s Republic of China; 2Basic Medical College, Heilongjiang University of Chinese Medicine, Harbin, Heilongjiang, 150040, People’s Republic of China; 3Key Laboratory of Basic and Application Research of Beiyao, Heilongjiang University of Chinese Medicine, Ministry of Education, Harbin, Heilongjiang, 150040, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rui Wang; Yanhong Wang, College of Pharmacy, Heilongjiang University of Chinese Medicine, Wenzheng Street, Harbin, Heilongjiang, 150040, People’s Republic of China, Tel/Fax +86-0451-87266893, Email wrdx@sina.com; wang.yanhong@163.comPurpose: Macrophages play a pivotal role in rheumatoid arthritis (RA) pathogenesis. Paeoniflorin, a traditional Chinese medication, reduces inflammation by suppressing immune cell activation and inducing synovial fibroblast apoptosis, attenuating RA disease progression. Despite the potential therapeutic benefits, free paeoniflorin has limitations, including low drug utilization, poor selectivity, and short half-life during administration. We aimed to develop and evaluate dextran sulfate-modified paeoniflorin pH-responsive lipid–polymer hybrid nanoparticles (Pae–PPNPs–DS) for targeted macrophage delivery and improved treatment efficacy in RA. The pH sensitivity is attributed to the incorporation of poly(cyclohexane-1,4-dimethylene ketal), which undergoes hydrolysis-triggered degradation under acidic conditions enabling passive targeting to inflammatory sites through pH-dependent drug release. Simultaneously, dextran sulfate serves as a ligand to actively target Scavenger receptor class A type I overexpressed on activated macrophages in RA synovium, achieving dual-targeted delivery via environmental responsiveness and ligand-receptor interaction.Methods: We developed dextran sulfate-modified Pae–PPNPs–DS, which exhibits dual capabilities of active macrophage targeting and pH-triggered drug release, to deliver paeoniflorin to macrophages and improve drug delivery at the joint inflammation site. Nanoparticle characterization, in vitro release behavior, stability, macrophage uptake, macrophage polarization pathway, phenotypic polarization, and therapeutic efficacy were evaluated in a rat model of RA.Results: Pae–PPNPs–DS had smooth surfaces, uniform particle sizes, physical stability, and pH-responsive characteristics. RAW264.7 macrophages showed enhanced Pae–PPNPs–DS uptake. Pae–PPNPs–DS effectively modulated the STAT signaling pathway and modulated macrophage polarization. Pae–PPNPs–DS inhibited the expression of TNF-α/IL-1β/iNOS/IL-6 (pro-inflammatory and M1 markers), while promoting IL-10/Arg-1/TGF-β (anti-inflammatory and M2 markers) secretion. Pathological analysis revealed that Pae–PPNPs–DS prevented synovial tissue proliferation, inhibited inflammatory cell infiltration, and exhibited therapeutic efficacy.Conclusion: Pae–PPNPs–DS actively target macrophages, regulate polarization through STAT pathway, and inhibit joint inflammation, suggesting its potential in treating RA. The study highlights the potential of pH-responsive nanocarriers as an innovative approach to treating autoimmune diseases.Plain Language Summary: Rheumatoid arthritis (RA) is a chronic condition that causes painful swelling and damage to the joints and is driven in part by overactive immune cells called macrophages, which produce harmful inflammation. Current treatments for RA can be expensive and have significant side effects, highlighting the need for new, safer therapies. Our study focused on improving how a natural compound called paeoniflorin is delivered to the inflamed joints of people with RA. Paeoniflorin has anti-inflammatory properties, but it does not last long in the body and is not very effective on its own. To address this, we developed tiny, specially designed carriers called nanoparticles to deliver paeoniflorin directly to the inflamed areas of the joints. These nanoparticles are coated with a material that helps them target macrophages and release the drug when they reach the acidic environment of the inflamed tissue. We tested our nanoparticles in vitro and in vivo with RA-like symptoms. The results were promising: the nanoparticles were endocytosed by macrophages, reduced harmful inflammation, and promoted healing. In rats, these nanoparticles reduced joint swelling and tissue damage more effectively than the drug on its own. They also showed good safety and stability. These findings suggest that this new delivery system could be a more effective and targeted way to treat RA, reducing the inflammation and pain caused by the disease while avoiding some of the side effects of current treatments. This approach could lead to better outcomes for people living with RA.Keywords: hybrid nanoparticles, macrophage targeting, pH-responsive drug delivery, targeted therapy, CIA model